Measuring Ethnic Stratification and its Effect on Trust in Africa - Roland Hodler; Sorawoot Srisuma; Alberto Vesperoni; Noémie Zurlinden (Center for Economic Studies and ifo Institute (CESifo), 2018)
We define and axiomatically characterize an index of ethnic stratification that measures the extent to which the hierarchy in socio-economic positions across the individuals of a society follows ethnolinguistic lines. This index generalizes the idea of between-group inequality to situations where data on economic and ethnolinguistic distances between pairs of individuals is available. We define an estimator of our index that takes the form of a second order U-statistic and has well-behaved statistical properties, and we show that ethnic stratification is empirically related to low levels of trust in other people and institutions at the local level in Africa.
Keywords: D31; D63; Z13; 330; inequality; ethnic diversity; ethnic fractionalization; trust